Lietuvių spaudos knygynai 1904–1918 m. - Raguotienė, Genovaitė (Knygotyra, 1995)
On May 7th, 1904 (according to the new calender) the repressive action of the Russian empire – the forty years of the ban of the Lithuanian press in Latin scripts – was abolished.Alter the restoration of the Lithuanian press new favourable conditions and circumstances came into being, and in all spheres of the Lithuanian social life new “accelerated” processes were going on.One of the important facts and results during the years 1904–1918 of the Lithuanian cultural development was the existence of a network of legal book-shops of the Lithuanian press.In the article various moments and aspects of the activities of the Lithuanian book-shops are analysed and the development of a network of these shops and other stationary establishments of the book trade are described.The information collected tells us that during the years 1904–1918 there existed about 90 Lithuanian book-shops. They worked simultaneously with book-shops belonging to the representatives of othor nations, partly also engaged in selling Lithuanian books; facts of cooperation between them are described.In the article are also analysed the cultural and commercial activities of the Lithuanian book-shops.Many of them acted not only as commercial institutions but perhaps more as institutions of enlightment and culture. The education of the people they regarded as their main task.The Lithuanian book-shops earned their existence with many difficulties. Their owners were mostly inexperienced in commercial matters and sometimes not able to withstand competition. To help themselves the book-shops traded other goods, mostly devotionals.In a separate section of this article the questions of assortment of literature are analysed (quantity, topics, genres etc.)Faetors which have stimulated and defermined the structure of the assortment are pointed out (publishing, censorship, political confrontation within the society etc.).The article acquaints you with the founders and owners of the described bookshops. Many of them have been Lithuanian cultural activists, formal illegal book distributors, writers. Only some of them were businessmen.As appendix statistical tables about the book-shops and their proprietors are added, about book-shops which were planned, but not established, as well.The history of the book-shops of the Lithuanian press which have been important factors in the development of the national culture has never been seriously studied and described. This article is the first attempt of such an extent and character to solve this problem.